2002
DOI: 10.1042/bj20020393
|View full text |Cite
|
Sign up to set email alerts
|

Rapid insertion of GLUT2 into the rat jejunal brush-border membrane promoted by glucagon-like peptide 2

Abstract: A possible role for GLUT2 transiently expressed in the rat jejunal brush-border membrane (BBM) under the influence of glucagon-like peptide 2 (GLP-2) was investigated using in vivo perfusion of the intestinal lumen as well as isolation of membrane proteins and immunohistochemistry. A 1 h vascular infusion of GLP-2 in vivo doubled the rate of fructose absorption and this increase could be blocked by luminal phloretin. Immunohistochemistry of frozen sections of rat jejunum showed the expression of GLUT2 in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
120
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 27 publications
9
120
1
1
Order By: Relevance
“…2). The distinct banding patterns confirmed that there was no cross-reactivity between antibody to one transporter and the other transporter; in addition, antibody to a sequence within the extracellular loop of GLUT2 gave similar results to the C-terminal antibody (8). All bands were eliminated by preincubation of antiserum with excess of the corresponding antigenic peptide, confirming the specificity of GLUT5 and the GLUT2 antisera for their target transporters (data not shown).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…2). The distinct banding patterns confirmed that there was no cross-reactivity between antibody to one transporter and the other transporter; in addition, antibody to a sequence within the extracellular loop of GLUT2 gave similar results to the C-terminal antibody (8). All bands were eliminated by preincubation of antiserum with excess of the corresponding antigenic peptide, confirming the specificity of GLUT5 and the GLUT2 antisera for their target transporters (data not shown).…”
Section: Resultssupporting
confidence: 61%
“…Support for the model of rapid, GLUT2-mediated up-regulation of sugar absorption has been provided by the observation that glucagon-like peptide 2 promotes rapid insertion of GLUT2 into the brush-border membrane (8). Moreover, a definitive confirmation of the model has recently been provided by the observation that when the intestine of wild type mice is challenged with sugars by gastric intubation, a large increase in fructose transport occurs within minutes; the increase in transport does not occur in GLUT2-null mice and is attributable entirely to GLUT2 (9).…”
mentioning
confidence: 99%
“…It is important to characterize whether GLP2 increases glucose incorporation in adipocytes when their response to insulin is impaired by obesity conditions. In fact, although there are conflicting reports regarding the alterations in the basal glucose uptake, most reports provide evidence that insulin-induced glucose incorporation is suppressed in the obese state (Talior et al 2003, Sancho et al 2006, Crowe et al 2008, and as GLP2 rapidly increases intestinal hexose absorption (Cheeseman 1997, Au et al 2002, it is not unlikely to hypothesize that it contributes to clearance of plasma glucose through an action on adipocytes. In addition or alternatively, GLP2 might influence and modulate the quality and quantity of secreted adipokines and the inflammatory state of adipose tissue.…”
Section: Mechanistic Insightmentioning
confidence: 99%
“…In fact, it induces crypt cell proliferation and inhibition of apoptosis, resulting in an increase of villous height and in the expansion of the absorptive mucosal surface in the small and large intestine (Drucker et al 1996, Tsai et al 1997, Drucker & Yusta 2014. Moreover, GLP2 increases the uptake of sugars by augmenting the activity and the expression of transporters (Cheeseman 1997, Au et al 2002, Ramsanahie et al 2004, Sueyoshi et al 2014 and by enhancing the expression of different enzymes involved in digestion (Brubaker et al 1997a, Petersen et al 2002. Evidence from studies on humans and animal models suggests that GLP2 also plays a role in lipid absorption.…”
Section: Overview On Glp2mentioning
confidence: 99%
“…A high sugar intake is a physiological regulator of this process, increasing monosaccharide uptake threefold in vivo (6). The recruitment of GLUT2 in BBM was also observed in conditions of increased calorie demand and glucagon-like peptide 2 treatment (7)(8)(9)(10)(11).…”
mentioning
confidence: 98%